Transdisciplinary Learning Based on Problem Identification of Design Computational Thinking - A Case Study of the Topic of Marine Debris - Chung-Hsiang Wang; Ko-Chiu Wu (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: The purpose of this study is to explore how design students can identify marine debris problems and generate insights through the computational thinking learning process to better develop design students’ ability to learn across domains. Methodology: Authors set up a transdisciplinary learning course of "Design Computational Thinking", trying to introduce the knowledge of marine debris in the humanities and environmental sustainability into the course, combining design thinking and computational thinking processes, and guiding students to think about and evaluate problems in stages and complete thematic design. Finally, through the achievement report, Expert assessment, and semi-structured interviews with students, content analyze and evaluate their learning effect. Findings: It was found that students were creative in the way to deal with marine debris problems. Computational thinking can have an impact on the design process. In the process of design decision-making, students can think and express hierarchically, and use core strategies to solve problems. Implications/Novel Contribution: This study attempted to bridge the research gap and provides a knowledge base for problem-solving through transdisciplinary and metacognitive learning. The combination of design thinking and computational thinking provides different levels of thinking models for problem-solving and generates insights.